2010
DOI: 10.4014/jmb.0904.04019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of potential probiotic- and starter properties of Pediococcus spp. Isolated from Turkish-type fermented sausages (sucuk)

Abstract: In this study, the metabolic activities of five strains of Pediococcus spp., in terms of the quantities they produced of lactic acid, hydrogen peroxide, exopolysaccharides, and proteolytic activity, were determined. Lactic acid levels produced by these strains were found to be in the range of 2.5-5.6 mg/ml. All strains produced hydrogen peroxide. The P. pentosaceus Z13P strain produced the maximum amount (0.25 mg/ml) of proteolytic activity. Exopolysaccharide (EPS) production by the Pediococcus strains during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…Similar results were obtained by different researchers for Pediococcus isolated from home‐made yogurt and Turkish dry‐fermented sausage (Beyatli et al . ; Yuksekdag and Aslim ). Resistance to the glycopeptide antibiotic vancomycin in Pediococcus and Lactobacillus strains isolated from sucuk were remarkable due to the use of vancomycin in many infections in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were obtained by different researchers for Pediococcus isolated from home‐made yogurt and Turkish dry‐fermented sausage (Beyatli et al . ; Yuksekdag and Aslim ). Resistance to the glycopeptide antibiotic vancomycin in Pediococcus and Lactobacillus strains isolated from sucuk were remarkable due to the use of vancomycin in many infections in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Acid production was assessed in sterilized skim milk (pH 6.8) and YEL (pH 7.2) media at 30°C, the media having been each inoculated, at a ratio of 0.2 ml/10 ml, with an active strain of Propionibacterium spp. Measurements of titratable acidity, expressed in milligrams of acid per milliliter, were performed on day 8 (11,39). The final culture pH and OD of the strains and culture media without inoculation (for negative control) were also determined.…”
Section: Methodsmentioning
confidence: 99%
“…Three Pediococcus strains were resistant to vancomycin at the highest amount, 2048 mg. P. pentosaceus and Pediococcus acidilactici strains from raw meat sausages were resistant against vancomycin [32]. Gotcheva et al reported that vancomycin resistance is an intrinsic property of many LAB [33].…”
Section: A-chymotrypsinmentioning
confidence: 99%